MOFs nano composite material as well as preparation method and application thereof
By combining sodium alginate and polyamide-amine with MOFs nanomaterials, polyamide-amine doped sodium alginate-MOFs nanocomposites are prepared, which solves the problems of difficult solid-liquid separation of powdered MOFs and excessive column pressure, and achieves high selective adsorption separation and good cycle and regeneration capabilities.
Patent Information
- Application Number
- CN202411614105.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
In practical applications, powdered MOFs have difficulty in separating solid-liquid, which leads to excessive column pressure when loading into separation columns, making them inconvenient to operate, which limits their application.
Polyamide-amine-doped sodium alginate-MOFs nanocomposites were prepared by organically combining sodium alginate and polyamide-amine with MOFs nanomaterials, and MOFs were synthesized on the surface of microspheres by in-situ growth method to form nanocomposites with high adsorption properties.
It has achieved high selective adsorption and separation of target compounds such as dyes, metal ions, antibiotics, natural product active ingredients, proteins, and polypeptides, solving the problems of difficulty in solid-liquid separation and excessive column pressure, and has good circulation and regeneration capabilities.
Smart Images

Figure CN119500076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanocomposite material preparation and adsorption separation, and specifically relates to the preparation and application of a MOFs nanocomposite material. Background Art
[0002] As a new type of organic-inorganic hybrid nanomaterial, metal-organic frameworks (MOFs) are self-assembled from rigid organic bridging ligands and metal ions. They have the advantages of highly ordered porous crystal structure, adjustable pore size, and easy chemical modification. They have been widely used in adsorption separation, biomedicine, carbon dioxide capture, catalysis, sensing, gas storage and other fields.
[0003] However, powdered MOFs have difficulty in solid-liquid separation in practical applications, and when used as a separation column, the column pressure will be too high, which leads to inconvenience in operation and limits its application. In order to solve the above problems, it is a good idea to combine nanomaterial MOFs with polymer materials to synthesize new polymer / MOFs composite materials. Summary of the invention
[0004] In view of the problems existing in the practical application of powdered MOFs, the present invention provides a method for preparing a MOFs nanocomposite material and its application, namely, a method for preparing a nanocomposite material using polyamide-amine and sodium alginate as raw materials, and using the prepared nanocomposite material in the field of adsorption and separation.
[0005] The MOFs nanocomposite material provided by the present invention comprises the following steps: 1) Dissolve sodium alginate in pure water to prepare a sodium alginate solution with a concentration of 0.5-10% (g / mL), and then add polyamide-amine to the sodium alginate solution to prepare a mixed solution containing 0.1-2% polyamide-amine; 2) Using anhydrous calcium chloride and / or calcium chloride dihydrate to prepare a calcium chloride solution with a concentration of 0.5-12% (g / mL); 3) The calcium chloride solution prepared in step 2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step 1) is slowly dripped into the calcium chloride solution drop by drop to prepare polyamide-amine doped sodium alginate microspheres, with a dripping speed of 0.5-1000 mL / min; 4) The prepared polyamide-amine doped sodium alginate microspheres are further immersed in the calcium chloride solution for 1-24 h to ensure complete gelation; then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water for 2-8 times, and vacuum dried at 40-90° C. for 4-48 h; 5) Dissolve the cobalt salt or zinc salt in a solvent (pure water, methanol or ethanol) to prepare a 1-50 mmol / L cobalt salt or zinc salt solution; then, add the polyamide-amine doped sodium alginate microspheres prepared in step 4) and shake at 10-80°C for 1-24 h; after the reaction is completed, filter and wash with pure water to obtain metal ion-loaded polyamide-amine doped sodium alginate microspheres; 6) Dissolve 2-methylimidazole in a solvent (pure water, methanol or ethanol) to prepare a 2-200 mmol / L 2-methylimidazole solution; then, add the polyamide-amine doped sodium alginate microspheres obtained in step 5) and shake at 10-80°C for 1-24 h; after the reaction is completed, filter and wash with pure water to obtain polyamide-amine doped sodium alginate microspheres loaded with ZIF, and vacuum dry at 40-90°C for 2-48 h to obtain polyamide-amine doped sodium alginate-MOFs nanocomposite materials.
[0006] Preferably, the concentration of the sodium alginate solution in step 1) is 2%, and the concentration of the polyamide-amine in the mixed solution is 0.2%.
[0007] Preferably, the concentration of the calcium chloride solution in step 2) is 1%.
[0008] Preferably, in step 3), the dropping speed of the sodium alginate and polyamide-amine mixed solution is 10 mL / min.
[0009] Preferably, in step 4), the polyamide-amine doped sodium alginate microspheres are continuously immersed in the calcium chloride solution for 16 h, washed with pure water for 3 times, and vacuum dried at 60° C. for 24 h.
[0010] Preferably, in step 5), the cobalt salt is cobalt nitrate hexahydrate or cobalt chloride hexahydrate, the zinc salt is zinc acetate dihydrate, the solvent is pure water, the concentration of the cobalt salt or zinc salt solution is 20 mmol / L, the shaking temperature is 25°C, the shaking time is 6 h, and the number of pure water washings is 3 times.
[0011] Preferably, in step 6), the solvent is pure water, the concentration of 2-methylimidazole is 50 mmol / L, the shaking temperature is 25° C., the shaking time is 12 h, and the number of pure water washings is 3 times.
[0012] The MOFs nanocomposite material prepared by the present invention can be used for selective adsorption and separation of dyes, metal ions, antibiotics, effective ingredients of natural products, proteins, polypeptides, etc. in liquid environments.
[0013] As a specific description of the embodiment, the dye is methylene blue, the metal ion is Pb(II), the antibiotic is amoxicillin, and the protein is bovine serum albumin.
[0014] The present invention organically combines natural polymer material sodium alginate, dendritic macromolecule polyamide-amine and MOFs nanomaterial, first synthesizes polyamide-amine doped sodium alginate microspheres, and then synthesizes MOFs by an in-situ growth method to prepare a new polymer / MOFs nanocomposite material. The surface of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared by the present invention has abundant hydroxyl groups, amino groups, carboxyl groups, and MOFs sites, showing excellent hydrophilicity and adsorption performance, and can be used for selective adsorption of dyes, metal ions, antibiotics, effective ingredients of natural products, proteins, polypeptides, etc. Moreover, by adjusting parameters such as the pH value of the solution, the surface properties of the nanocomposite material are regulated to achieve highly selective adsorption and separation of target compounds. The surface of the polyamide-amine doped sodium alginate-MOFs nanocomposite material of the present invention has a large number of groups such as hydroxyl groups, amino groups, amide groups, carboxyl groups, metal ions, etc., which is conducive to subsequent related functional modification, and a series of nanocomposite materials with different functional groups, specific surface areas, pore volumes and average pore sizes are prepared, which broadens its application field and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 : FTIR images of polyamide-amine doped sodium alginate-MOFs nanocomposite.
[0016] Figure 2 : XPS full spectrum of polyamide-amine doped sodium alginate-MOFs nanocomposite.
[0017] Figure 3 : Swelling properties of polyamidoamine doped sodium alginate-MOFs nanocomposites.
[0018] Figure 4 : Isoelectric point diagram of polyamidoamine doped sodium alginate-MOFs nanocomposites.
[0019] Figure 5 : Adsorption properties of polyamidoamine doped sodium alginate-MOFs nanocomposites.
[0020] Figure 6 : Adsorption selectivity results of polyamide-amine doped sodium alginate-MOFs nanocomposites.
[0021] Figure 7 : Graph of the recycling performance of polyamide-amine doped sodium alginate-MOFs nanocomposites. DETAILED DESCRIPTION
[0022] The sodium alginate used in the present invention is a natural polysaccharide polymer, which mainly exists in brown algae plants. It is a renewable biomass macromolecular compound with abundant reserves in nature. Its main components are β-D-mannuronic acid and α-L-guluronic acid. There are a large number of active groups such as carboxyl and hydroxyl groups in the structure of sodium alginate. Polyamide-amine (PAMAM) has a highly branched molecular structure and rich functional groups such as amide and amino groups.
[0023] The present invention uses polyamide-amine dendrimers with a highly branched molecular structure, rich functional groups such as amides and amino groups, and controllable internal nanocavities as doping components to prepare polyamide-amine doped sodium alginate microspheres with stronger hydrophilicity and more functional groups, and then uses an in-situ growth method to synthesize ZIF-8 or ZIF-67 with a nanostructure on the surface of the microspheres to prepare polyamide-amine doped sodium alginate-MOFs nanocomposite materials with a larger specific surface area, more adsorption sites and a higher exposure ratio, stronger adsorption performance, and a multi-level pore structure.
[0024] By adjusting the pH and other parameters, the interaction force between the polyamide-amine doped sodium alginate-MOFs nanocomposite material and the target molecule is changed, and the highly selective adsorption and separation of the target molecule can be achieved. The polyamide-amine doped sodium alginate-MOFs nanocomposite material of the present invention has good recycling ability and can be reused after being eluted with an eluent, which greatly reduces the cost.
[0025] The polyamide-amine doped sodium alginate-MOFs nanocomposite material of the present invention can effectively solve the problems of difficulty in solid-liquid separation of powdered MOFs in practical applications, excessive column pressure when used as a separation column, inconvenient operation, and limited application, etc., which is conducive to the industrial application of MOFs materials. Moreover, sodium alginate, a main preparation material thereof, is a natural polymer material, which is cheap, easily available, green and environmentally friendly. The preparation process does not cause pollution to the environment, and has broad application prospects.
[0026] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0027] Example 1 (1) Prepare a 2.0% sodium alginate solution by dissolving 2.0 g of sodium alginate in 100 mL of pure water to obtain a clear solution. Then, add 0.2 g of polyamide-amine to the sodium alginate solution to obtain a mixed solution containing 0.2% polyamide-amine.
[0028] (2) Prepare a 3.33% calcium chloride solution by dissolving 3.33 g of anhydrous calcium chloride in 100 mL of pure water until the solution becomes clear.
[0029] (3) The calcium chloride solution prepared in step (2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step (1) is slowly dripped into the calcium chloride solution drop by drop at a dripping speed of 10 mL / min.
[0030] (4) After the dripping is completed, the obtained polyamide-amine doped sodium alginate microspheres are further immersed in the calcium chloride solution for 12 h to ensure complete gelation. Then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water for 4 times, and vacuum dried at 60 °C for 24 h.
[0031] (5) Dissolve 1.43 g of cobalt chloride hexahydrate in 300 mL of ethanol to prepare a 20 mmol / L cobalt salt solution. Then, add the polyamide-amine doped sodium alginate microspheres prepared in step (4) and shake at 25°C for 6 h. After the reaction is completed, filter and wash with pure water three times to obtain metal ion-loaded polyamide-amine doped sodium alginate microspheres.
[0032] (6) Dissolve 1.13 g of 2-methylimidazole in 300 mL of ethanol to prepare a 50 mmol / L 2-methylimidazole solution. Then, add the microspheres obtained in step (5) and shake at 25°C for 12 h. After the reaction is completed, filter and wash with pure water three times to obtain polyamide-amine doped sodium alginate microspheres loaded with ZIF-67.
[0033] (7) Highly selective adsorption method: The synthesized polyamide-amine doped sodium alginate-MOFs nanocomposite was placed in a methylene blue aqueous solution, the pH of the solution was adjusted to 10, the mass ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the solution was controlled to be 1:1000, and the adsorption was carried out by stirring at room temperature. The adsorption capacity was 712 mg / g; the polyamide-amine doped sodium alginate-MOFs nanocomposite adsorbed with methylene blue was placed in a hydrochloric acid-ethanol solution (the volume ratio of 0.1 mol / L hydrochloric acid to ethanol was 1:1, and ethanol was anhydrous ethanol), the volume ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the hydrochloric acid-ethanol solution was controlled to be 1:1000, and the adsorption was carried out by stirring at room temperature. The highly selective recovery of methylene blue and the reuse of the polyamide-amine doped sodium alginate-MOFs nanocomposite can be achieved. The material was used for adsorption again, and its adsorption capacity can still reach 696 mg / g.
[0034] Example 2 (1) Prepare a 4.0% sodium alginate solution by dissolving 400 g of sodium alginate in 10 L of pure water to obtain a clear solution. Then, add 150 g of polyamide-amine to the sodium alginate solution to obtain a mixed solution containing 1.5% polyamide-amine.
[0035] (2) Prepare a 10.0% calcium chloride solution by dissolving 1.3 kg of calcium chloride dihydrate in 10 L of pure water to form a clear solution.
[0036] (3) The calcium chloride solution prepared in step (2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step (1) is slowly dripped into the calcium chloride solution drop by drop at a dripping speed of 100 mL / min.
[0037] (4) After the dripping is completed, the obtained polyamide-amine doped sodium alginate microspheres are further immersed in the calcium chloride solution for 16 h to ensure complete gelation. Then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water for 5 times, and vacuum dried at 70 °C for 30 h.
[0038] (5) Dissolve 265 g of zinc acetate dihydrate in 30 L of pure water to prepare a 40 mmol / L zinc salt solution. Then, add the polyamide-amine doped sodium alginate microspheres prepared in step (4) and shake at 35°C for 18 h. After the reaction is completed, filter and wash with pure water 4 times to obtain metal ion-loaded polyamide-amine doped sodium alginate microspheres.
[0039] (6) Dissolve 226 g of 2-methylimidazole in 30 L of pure water to prepare a 100 mmol / L 2-methylimidazole solution. Then, add the microspheres obtained in step (5) and shake at 35°C for 20 h. After the reaction is completed, filter and wash with pure water 4 times to obtain polyamide-amine doped sodium alginate microspheres loaded with ZIF-8.
[0040] (7) Highly selective adsorption method: The synthesized polyamide-amine doped sodium alginate-MOFs nanocomposite was placed in a Pb(II) aqueous solution, the pH of the solution was adjusted to 5, the mass ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the solution was controlled to be 1:1500, and the adsorption was carried out by stirring at room temperature. The adsorption capacity was 587 mg / g; the polyamide-amine doped sodium alginate-MOFs nanocomposite adsorbed with Pb(II) was placed in a hydrochloric acid-ethanol solution (the volume ratio of 0.8 mol / L hydrochloric acid to ethanol was 1:3, and the ethanol was 95% ethanol), the volume ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the hydrochloric acid-ethanol solution was controlled to be 1:1500, and the elution was carried out by stirring at room temperature. The highly selective recovery of Pb(II) and the reuse of the polyamide-amine doped sodium alginate-MOFs nanocomposite can be achieved. The material was used for adsorption again, and its adsorption capacity can still reach 556 mg / g.
[0041] Example 3 (1) 6 kg of sodium alginate was completely dissolved in 100 L of pure water to form a clear solution to prepare a 6.0% sodium alginate solution. 1.0 kg of polyamide-amine was then added to the sodium alginate solution to obtain a mixed solution containing 1.0% polyamide-amine.
[0042] (2) Prepare a 6.7% calcium chloride solution by dissolving 8.8 kg of calcium chloride dihydrate in 100 L of pure water to obtain a clear solution.
[0043] (3) The calcium chloride solution prepared in step (2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step (1) is slowly dripped into the calcium chloride solution drop by drop at a dripping speed of 800 mL / min.
[0044] (4) After the dripping is completed, the obtained polyamide-amine doped sodium alginate microspheres are further immersed in the calcium chloride solution for 22 h to ensure complete gelation. Then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water for 7 times, and vacuum dried at 80 °C for 45 h.
[0045] (5) Dissolve 1.21 kg of zinc chloride in 600 L of methanol to prepare a 30 mmol / L zinc salt solution. Then, add the polyamide-amine doped sodium alginate microspheres prepared in step (4) and shake at 45°C for 22 h. After the reaction is completed, filter and wash with pure water 6 times to obtain metal ion-loaded polyamide-amine doped sodium alginate microspheres.
[0046] (6) Dissolve 3.45 kg of 2-methylimidazole in 600 L of methanol to prepare a 150 mmol / L 2-methylimidazole solution. Then, add the microspheres obtained in step (5) and shake at 45°C for 22 h. After the reaction is completed, filter and wash with pure water 6 times to obtain polyamide-amine doped sodium alginate microspheres loaded with ZIF-8.
[0047] (7) Highly selective adsorption method: The synthesized polyamide-amine doped sodium alginate-MOFs nanocomposite was placed in an aqueous solution of amoxicillin, the pH of the solution was adjusted to 9, the mass ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the solution was controlled to be 1:1800, and the adsorption was carried out by stirring at room temperature. The adsorption capacity was 652 mg / g; the polyamide-amine doped sodium alginate-MOFs nanocomposite adsorbed with amoxicillin was placed in a hydrochloric acid-ethanol solution (the volume ratio of 0.4 mol / L hydrochloric acid to ethanol was 4:1, and the ethanol was 95% ethanol), the volume ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the hydrochloric acid-ethanol solution was controlled to be 1:1200, and the elution was carried out by stirring at room temperature. The highly selective recovery of amoxicillin and the reuse of the polyamide-amine doped sodium alginate-MOFs nanocomposite can be achieved. The material was used for adsorption again, and its adsorption capacity can still reach 607 mg / g.
[0048] Example 4 (1) 20.0 kg of sodium alginate was completely dissolved in 250 L of pure water to obtain a clear solution to prepare an 8.0% sodium alginate solution. 1.25 kg of polyamide-amine was then added to the sodium alginate solution to obtain a mixed solution containing 0.5% polyamide-amine.
[0049] (2) Prepare a 5.5% calcium chloride solution by dissolving 13.75 g of anhydrous calcium chloride in 250 L of pure water to obtain a clear solution.
[0050] (3) The calcium chloride solution prepared in step (2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step (1) is slowly dripped into the calcium chloride solution drop by drop at a dripping speed of 1000 mL / min.
[0051] (4) After the dripping is completed, the obtained polyamide-amine doped sodium alginate microspheres are further immersed in the calcium chloride solution for 24 h to ensure complete gelation. Then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water for 8 times, and vacuum dried at 90 °C for 48 h.
[0052] (5) Dissolve 8.8 kg of cobalt nitrate hexahydrate in 600 L of pure water-ethanol mixed solution (1:1) to prepare a 50 mmol / L cobalt salt solution. Then, add the polyamide-amine doped sodium alginate microspheres prepared in step (4) and shake at 55°C for 24 h. After the reaction is completed, filter and wash with pure water 8 times to obtain metal ion-loaded polyamide-amine doped sodium alginate microspheres.
[0053] (6) Dissolve 9.0 kg of 2-methylimidazole in 600 L of a 1:1 pure water-ethanol mixed solution to prepare a 200 mmol / L 2-methylimidazole solution. Then, add the microspheres obtained in step (5) and shake at 65°C for 24 h. After the reaction is completed, filter and wash with pure water 8 times to obtain polyamide-amine doped sodium alginate microspheres loaded with ZIF-67.
[0054] (7) Highly selective adsorption method: The synthesized polyamide-amine doped sodium alginate-MOFs nanocomposite was placed in a bovine serum albumin aqueous solution, the pH of the solution was adjusted to 4.0, the mass ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the solution was controlled to be 1:500, and the adsorption was carried out by stirring at room temperature. The adsorption capacity was 461 mg / g; the polyamide-amine doped sodium alginate-MOFs nanocomposite adsorbed with bovine serum albumin was placed in a hydrochloric acid-ethanol solution (the volume ratio of 0.2 mol / L hydrochloric acid to ethanol was 2:1, and the ethanol was 95% ethanol), the volume ratio of the polyamide-amine doped sodium alginate-MOFs nanocomposite to the hydrochloric acid-ethanol solution was controlled to be 1:500, and the adsorption was carried out by stirring at room temperature. The highly selective recovery of bovine serum albumin and the reuse of the polyamide-amine doped sodium alginate-MOFs nanocomposite can be achieved. The material was used for adsorption again, and its adsorption capacity can still reach 408 mg / g.
[0055] Example 5: Material characterization of prepared polyamidoamine doped sodium alginate-MOFs nanocomposite 1. FTIR The polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1 was characterized by FTIR. Figure 1 It can be seen that the FTIR spectrum shows infrared absorption peaks of characteristic groups such as hydroxyl, carboxyl, amide, amino, and N-Co, proving the successful preparation of the nanocomposite material.
[0056] 2. XPS XPS was used to characterize the surface chemistry of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1. Figure 2It can be seen that the XPS full spectrum shows the binding energies of C1s, O1s, N1s, and Co2p, indicating that the nanocomposite material contains polyamidoamine dendrimers and ZIF-67, so the material is successfully prepared.
[0057] 3. Swelling The swelling properties of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1 were systematically investigated under pure water and different pH conditions. Figure 3 It can be seen that in pure water, swelling equilibrium is reached after 60 minutes, and the swelling rate of the nanocomposite material is 36.6%. In pure water with different pH values, under alkaline conditions, the swelling rate of the nanocomposite material is high and relatively stable, up to 46.2%. The results show that the material has relatively good swelling and stability.
[0058] 4. pH PZC Determination The pH value (pH 2.0) at which the net surface charge of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1 is equal to zero was determined by the pH drift method. PZC ).from Figure 4 It can be seen that pH PZC =7.63, indicating that when pH < 7.63, the surface of the material is positively charged, which is conducive to the adsorption and separation of negatively charged samples, and when pH > 7.63, the surface of the material is negatively charged, which is conducive to the adsorption and separation of positively charged samples. Therefore, the composite material has a high adsorption selectivity.
[0059] The characterization results of the MOFs nanocomposites prepared in Examples 2-4 demonstrate that the MOFs nanocomposites prepared by the method of the present invention have similar characterization characteristics.
[0060] Example 6: Adsorption effect of nanocomposite materials 1. Adsorption capacity Taking methylene blue as the target molecule, the effects of adsorption time, initial concentration, ionic strength, pH value and other parameters on the adsorption capacity of the polyamidoamine-doped sodium alginate-MOFs nanocomposite prepared in Example 1 were systematically evaluated. The specific results are shown in Figure 5 . The results show that with the increase of adsorption time, the adsorption capacity gradually increases, and the adsorption equilibrium is reached after 10 h; with the increase of the initial concentration of methylene blue, the adsorption capacity increases almost linearly; the presence of metal ions in the solution has little effect on the adsorption capacity, indicating that the prepared composite material has good applicability; with the increase of the pH value of the solution, the adsorption capacity increases, and when pH=10, the adsorption capacity is as high as 725 mg / g. The above results show that the nanocomposite material has excellent adsorption properties.
[0061] 2. Adsorption selectivity With methylene blue and methyl orange as target molecules, the adsorption selectivity of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1 at different pH values was evaluated, and the specific results are shown in Appendix 6. The results show that when the pH value of the solution is 10, the adsorption selectivity reaches the maximum, and the selectivity factor is as high as 531. This result shows that the prepared nanocomposite has good adsorption selectivity.
[0062] 3. Cyclic performance Taking methylene blue as the target molecule, under the optimal conditions, the recycling performance of the polyamide-amine doped sodium alginate-MOFs nanocomposite prepared in Example 1 was evaluated. The specific results are shown in the attached Figure 7 The results show that when the number of cycles is 4, the adsorption capacity of the nanocomposite material can still reach more than 80% of the initial adsorption capacity. This result shows that the prepared nanocomposite material has good recycling performance and has good application prospects.
[0063] The adsorption results of the MOFs nanocomposites prepared in Examples 2-4 demonstrate that the MOFs nanocomposites prepared by the method of the present invention have similar adsorption effects.
[0064] Although the preferred embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are merely illustrative and not restrictive. Under the guidance of the present invention, those skilled in the art, without departing from the scope of the present invention and the scope of protection of the claims, shall make changes, modifications, substitutions, combinations, and simplifications, which shall be equivalent replacement modes, and all of which belong to the protection scope of the present invention.
Claims
1. A MOFs nanocomposite material, characterized in that: The preparation method of the MOFs nanocomposite material comprises the following steps: 1) dissolving sodium alginate in pure water to prepare a sodium alginate solution, and then adding polyamide-amine to the sodium alginate solution to prepare a mixed solution containing polyamide-amine; 2) Using anhydrous calcium chloride and / or calcium chloride dihydrate to prepare a calcium chloride solution; 3) The calcium chloride solution prepared in step 2) is continuously and slowly stirred, and then the sodium alginate and polyamide-amine mixed solution prepared in step 1) is slowly and dropwise added into the calcium chloride solution to prepare polyamide-amine-doped sodium alginate microspheres; 4) The prepared polyamide-amine doped sodium alginate microspheres are further immersed in a calcium chloride solution to completely gel; then, the obtained polyamide-amine doped sodium alginate microspheres are filtered, washed with pure water, and vacuum dried; 5) dissolving the cobalt salt or zinc salt in a solvent to prepare a cobalt salt or zinc salt solution; then, adding the polyamide-amine doped sodium alginate microspheres prepared in step 4), shaking for reaction, filtering after the reaction is completed, and washing with pure water to obtain polyamide-amine doped sodium alginate microspheres loaded with metal ions; 6) Dissolving 2-methylimidazole in a solvent to prepare a 2-methylimidazole solution; then, adding the polyamide-amine doped sodium alginate microspheres obtained in step 5), shaking for reaction, filtering after the reaction is completed, washing with pure water, and preparing polyamide-amine doped sodium alginate microspheres loaded with ZIF; after vacuum drying, obtaining polyamide-amine doped sodium alginate-MOFs nanocomposite materials.
2. The MOFs nanocomposite material according to claim 1, characterized in that: The concentration of the sodium alginate solution in 1) is 0.5-10%, and the concentration of the polyamide-amine in the mixed solution is 0.1-2%.
3. The MOFs nanocomposite material according to claim 1, characterized in that: The concentration of the calcium chloride solution in the step 2) is 0.5-12%.
4. The MOFs nanocomposite material according to claim 1, characterized in that: The dropping speed in the step 3) is 0.5-1000 mL / min.
5. The MOFs nanocomposite material according to claim 1, characterized in that: The solvent in 5) or 6) is pure water, methanol or ethanol.
6. The MOFs nanocomposite material according to claim 1, characterized in that: The concentration of the cobalt salt or zinc salt solution in 5) is 1-50 mmol / L.
7. The MOFs nanocomposite material according to claim 1, characterized in that: The concentration of the 2-methylimidazole solution in 6) is 2-200 mmol / L.
8. Use of the MOFs nanocomposite material according to claim 1 in adsorbing dyes, metal ions, antibiotics, active ingredients of natural products, proteins or peptides in a liquid environment.
9. A method for adsorbing dyes, metal ions, antibiotics, active ingredients of natural products, proteins or polypeptides in a liquid environment, characterized in that: The method described is to use the MOFs nanocomposite material described in claim 1 as an adsorption material for adsorption.
10. An adsorption product, characterized in that: The adsorption product contains the MOFs nanocomposite material according to claim 1.